IMPLEMENTATION OF CLASSICAL GUIDANCE WITH MINI CINEMA TO IMPROVE CAREER SELF EFFICACY IN CLASS XI MIPA 3 SMA NEGERI 1 MOJOSARI - Lailatul Nurul Khasanah (Sean Institute, 2022)
Self-efficacy is a person's inner belief in his own ability to organize and take action in order to achieve the desired results. The problem of low self-efficacy towards career selection is something that is serious because it is related to the future and aspirations of students. This study uses classical guidance services by utilizing mini cinemas to increase low self-efficacy towards career selection in Class XI MIPA 3 students at SMA Negeri 1 Mojosari. The purpose of this study is to describe the low level of self-efficacy towards career selection before and after being given classical guidance by using a mini cinema. This research is a classroom action research. The research procedure in this study includes planning, action, observation and reflection. This study consisted of two cycles with four meetings. The population in this study were all students of Class XI MIPA 3 at SMA Negeri 1 Mojosari, which consisted of 34 students. The results showed that the 34 students who became the research sample had a self-efficacy level of 52.25% (low category) before receiving classical guidance services using mini cinemas. After obtaining classical guidance services by using mini cinemas, the average percentage of self-efficacy towards career selection increases and enters the high category. There are differences in the level of self-efficacy for career selection before and after the implementation of classical guidance services using mini cinemas.